Analisis Kepribadian Tokoh-Tokoh Dalam Novel Gejolak Dalam Awan Karya Desni Intan Suri - Lestari, Putri Ayu; Meliasanti, Ferina; Sutri, Sutri (Peneliti.net, 2024)
Literary works are works of art that are closely related to life. Literary works are created by authors through writing using aesthetic language. A literary work is not completely taken from real life, but has been processed by the author through his imagination. This study aims to describe the intrinsic elements and personalities of the characters in Desni Intan Suri's novel Gejolak Dalam Awan and their use as teaching materials for high school level. Novel This method is used by researchers to analyze the intrinsic elements in the novel Gejolak Dalam Awan by Desni Intan Suri, in the form of: (1) Theme, (2) Plot and Plotting, (3) Characters and Characterizations, (4) Setting, (5) ) Point of View, (6) Language, (7) Moral. Then analyze the personality structure of the characters in Desni Intan Suri's novel Turmoil in the Clouds with Freud's Psychoanalytic the.